2011
DOI: 10.1088/0964-1726/20/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Dissipativity analysis of the base isolated benchmark structure with magnetorheological fluid dampers

Abstract: This paper investigates the dissipativity and performance characteristics of the semiactive control of the base isolated benchmark structure with magnetorheological (MR) fluid dampers. Previously, the authors introduced the concepts of dissipativity and dissipativity indices in the semiactive control of structures with smart dampers and studied the dissipativity characteristics of simple structures with idealized dampers. To investigate the effects of semiactive controller dissipativity characteristics on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The inherently dissipative nature of the force produced by the MR damper (e.g., [35]) permits a designer to choose among several control methods without any concerns about the stability of the control system. This allows much freedom in the selection of a control technique for MR dampers implemented in real structures.…”
Section: Discussionmentioning
confidence: 99%
“…The inherently dissipative nature of the force produced by the MR damper (e.g., [35]) permits a designer to choose among several control methods without any concerns about the stability of the control system. This allows much freedom in the selection of a control technique for MR dampers implemented in real structures.…”
Section: Discussionmentioning
confidence: 99%
“…When z y1 = h/2 − τ y (H)/m > 0, the MR fluid flows with a floating core, submitting (10), (12), (13) into 15is…”
Section: Analysis Of Flow Velocity In Working Gapmentioning
confidence: 99%
“…It was defined that the force increases practically linearly when increasing strength of the magnetic field and when increasing piston speed. Erkus and Johnson [13] investigated the dissipativity and performance characteristics of the semiactive control of the base-isolated benchmark structure with MR dampers. Rajamani and Larparisudthi [14] proposed a vibration control model for MR isolating damper.…”
Section: Introductionmentioning
confidence: 99%
“…Weber et al [11] studied the performance of structure equipped with a semiactive friction pendulum against the seismic loading and determined the optimal friction coefficient of isolation system for minimizing the structure acceleration. Magnetorheological (MR) damper is also another effective semiactive control system considered separately [12,13] or together with the base isolation system for controlling the structural response [14][15][16][17][18]. Ramallo et al [19] demonstrated the effectiveness of adding a MR damper to conventional isolated structures by achieving notable decreases in base drifts compared to passive systems.…”
Section: Introductionmentioning
confidence: 99%